(untitled) (Hoboken, NJ, 2004)
While asthma can't be cured, it can be treated and controlled so that your child can enjoy a healthier, more active life. In this important guide, the experts at the top-ranked children's hospital in the United States clearly explain what asthma is and how parents, caregivers, and young patients can manage it successfully. The Children's Hospital of Philadelphia Guide to Asthma features the most up-to-date information on the disease and the keys to optimal preventive treatment-controlling environmental conditions that trigger symptoms, making a proactive medical treatment plan, and consistently putting it into action at the first sign of trouble. You'll discover how asthma is diagnosed, what the common triggers are, how to select the best asthma medicines, and how to protect your child in and away from your home to help him or her live a fulfilling childhood that is as symptom-free as possible.
Keywords: Asthma in children,Asthma in children,Hen suyễn ở trẻ em,Hen suyễn ở trẻ em; Treatment,Điều trị